2005
DOI: 10.1080/14992020500146450
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of aging on event-related potentials during a linguistic monitoring task

Abstract: Two groups of adults, one young and one elderly, were compared on a dichotic task in which continuous speech was monitored for grammatically and semantically anomalous words. Event-related potentials (ERPs) elicited by these anomalies were analyzed in terms of peak amplitude and peak latency of the evoked late-positive component (LPC). Results showed that while LPC peak amplitudes were overall reduced for the group of seniors, LPC peak latencies were similar between both groups of listeners. These findings are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…By contrast, the amplitude of response to the negative images exhibited a gradual, consistent, and significant linear decrease beginning in the 20s and continuing until late life. So although there appears to be some generalized age-related dampening for the LPP waveform—similar to the dampening of other late positive ERP components that are elicited by nonevaluative expectancy violations (e.g., Federmeier, Van Petten, Schwartz, & Kutas, 2003; Jerger & Martin, 2005), including the P300 (reviewed by Kok, 2000)—the results of the present study demonstrate an interaction between age and emotional valence. Specifically, the LPP responses to positive and negative information exhibited differential age-related patterns of change.…”
Section: Discussionsupporting
confidence: 62%
“…By contrast, the amplitude of response to the negative images exhibited a gradual, consistent, and significant linear decrease beginning in the 20s and continuing until late life. So although there appears to be some generalized age-related dampening for the LPP waveform—similar to the dampening of other late positive ERP components that are elicited by nonevaluative expectancy violations (e.g., Federmeier, Van Petten, Schwartz, & Kutas, 2003; Jerger & Martin, 2005), including the P300 (reviewed by Kok, 2000)—the results of the present study demonstrate an interaction between age and emotional valence. Specifically, the LPP responses to positive and negative information exhibited differential age-related patterns of change.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, LPC waveform morphology is more variable in a complex listening paradigm, such as dichotic listening (Jerger and Lew, 2004). Using a dichotic task in which grammatically and semantically anomalous words were employed, Jerger and Martin (2005) showed that LPC peak amplitude was reduced in senior adults (68-77 yr) as compared to young adults (18-33 yr), but no significant differences in LPC peak latencies were found between the two groups. Consistent with a behavioral dichotic rightear advantage, increased LPC amplitude and shorter latencies have been shown in the right ear as compared to the left ear in the elderly (Jerger et al, 2000;Greenwald and Jerger, 2001;Jerger and Martin, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Threshold elevation can account for nearly all of the changes in speech perception with age in quiet or in less demanding listening environments (Humes, 1996). But in complex perceptual tasks, older listeners are more likely to demonstrate interhemispheric differences, changes in event-related potentials (Jerger and Martin, 2005), and suprathreshold deficits in addition to the effects of reduced audibility. It is unclear exactly which factors account for this (Gordon-Salant and Fitzgibbons, 1997;Pichora-Fuller and Souza, 2003), though several possibilities will be discussed below.…”
mentioning
confidence: 99%